Behavior of Andean puma Puma concolor (Linnaeus, 1771) in captivity under an environmental enrichment programme in the zoo «Taraccasa» (Apurímac, Peru) - Morales Mijahuanca, Cristian J. (2017)
An environmental enrichment programme was applied to pumas (Pumas concolor) of the Taraccasa Zoological Park in Abancay (Apurímac, Peru) to monitor behavioural changes. Four pumas or cougars (three females, one male) from 3 to 9 years old were observed. Four types of environmental enrichment were used: physical (wooden stools, tree trunks), food (equine meat, balanced feed for cats), sensorial (sacks with aromatic essences and spices, urine of foxes and deer), and social (balls made with equine skin). The study considered the stage prior to environmental enrichment (24 days) and the stage during environmental enrichment (24 days). The behaviours were recorded with video camera between 09:00 to 12:00 and between 16:00 to 18:00. Individual behaviours with a significant increase were body care, locomotion, observation, exploration, search (p<0.001) and reduction of abnormal behaviour such as pacing (p<0.001) was also observed, while group behaviours that increased were approximation and marking (p<0.001), and chasing decreased (p<0.001). It is concluded that the environmental enrichment programme applied to the pumas had a positive effect, increasing normal activity and social behaviours, and reducing stereotypy.